Analytical Methods to Assess Polyphenols, Tannin Concentration, and Astringency in Hard Apple Cider - Stephan Sommer; Andrea Faeth Anderson; Seth D. Cohen (Applied Sciences, 2022)
The production of hard apple cider frequently involves considerations based on the balance between fermentable sugars and titratable acidity and/or pH. However, these are not the only attributes that influence the sensory properties of cider. Various groups of polyphenols and tannins influence bitterness, astringency, and mouthfeel, as well as color of the product. In this study, 19 single variety hard apple ciders were evaluated using analytical methods originally developed for wines. The aim was to determine how the cider matrix affects the functionality of each method. The results indicate that most assays work with sufficient accuracy with the exception of protein precipitation methods. Due to interferences of polysaccharides with the protein reaction, those assays are poorly reproducible and do not reflect the actual polyphenol or tannin concentration. The analytical determination of astringency is also influenced by this interference, since it traditionally uses the concept of protein precipitation as well. Liquid chromatography as a selective method can be readily applied to cider. Other colorimetric methods or non-protein precipitation methods, such as the Folin-Ciocalteu assay, the Methylcellulose Precipitation assay, and the Iron-Reactive Phenolics assay, can be used to classify apple ciders and make decisions based on the desired bitterness and astringency profile.